Feministische Visionen Vor und Nach 1989 : - Aleksander, Karin.,Auga, Ulrike.,Dvorakk, Elisaveta.,Heft, Kathleen.,Jähnert, Gabriele.,Schimkat, Heike.,Ilsen, Almut.,Chołuj, Bożena.,Dölling, Irene.,Nickel, Hildegard Maria. (Verlag Barbara Budrich, 2022)
How did gender discourses challenge social relations before and after 1989? How did actors intervene in powerful orders? How are feminist visions incorporated into contemporary activisms? This volume examines feminist, queer, and artistic practices of resistance as well as media discourses and attributions of GDR gender images from intersectional, postcolonial, and post-secular perspectives. In addition, the development of gender studies in Eastern Europe will be examined. Wie forderten Geschlechterdiskurse vor und nach 1989 die gesellschaftlichen Verhältnisse heraus? Wie intervenierten Akteur*innen in machtvolle Ordnungen? Wie werden feministische Visionen in gegenwärtige Aktivismen aufgenommen? Der Band untersucht feministische, queere und künstlerische Widerstandspraxen sowie Mediendiskurse und Selbst- und Fremdzuschreibungen von DDR-Geschlechterbildern aus intersektionalen, postkolonialen und postsäkularen Perspektiven. Zudem wird die Entwicklung der Gender Studies in Osteuropa in den Blick genommen.
Keywords: Friedliche Revolution; Revolution 1989; 1989; GDR; DDR; gender studies; East Germany; Geschlechterforschung; Ostdeutschland; othering; feminism; foreign attributions; Fremdzuschreibungen; gender relations; Geschlechterverhältnis; Frauenbewegung; women's movement; resistance; Widerstand; intersectionality; Intersektionalität; queer theory; Queer-Theorie; media; Medien; discourse; Diskurs; Eastern Europe; Osteuropa; Poland; Polen; Czech Republic; Tschechien; Hungary; Ungarn; Feminism & feminist theory